Neoangiogenesis of human mesenchymal stem cells transfected with peptide-loaded and gene-coated PLGA nanoparticles. (January 2016) - Park, Ji Sun; Yang, Han Na; Yi, Se Won; Kim, Jae-Hwan; Park, Keun-Hong
Abstract: Several factors are involved in angiogenesis. To form new blood vessels, we fabricated vehicles carrying an angiogenesis-related peptide (apelin) and gene (vascular endothelial growth factor (VEGF)165 ) that were internalized by human mesenchymal stem cells (hMSCs). These non-toxic poly-(DL)-lactic-co-glycolic acid (PLGA) nanoparticles (NPs) easily entered hMSCs without cytotoxicity. The negatively charged outer surface of PLGA NPs can be easily complexed with highly positively charged polyethylenimine (PEI) to deliver genes into cells. PLGA NPs complexed with PEI could be coated with negatively charged VEGF plasmid DNA and loaded with apelin. The physical characteristics of these PLGA NPs were determined by size distribution, gel retardation, and morphological analyses. Transfection of VEGF-coated apelin-loaded PLGA NPs resulted in the differentiation of hMSCs into endothelial cells and vascular formation in Matrigel in vitro . Following injection of hMSCs transfected with these PLGA NPs into an ischemic hind limb mouse model, these cells differentiated into endothelial cells and accelerated neovascularization.